Associations between chronic pelvic pain and psychiatric disorders and symptoms (Archives of Clinical Psychiatry, 2015)
Background Chronic pelvic pain (CPP) is a complex condition wich is associated with emotional factors, specially depression and anxiety. Objectives To make a systematic review to provide a detailed summary of relevant literature on the association between CPP and different psychiatric disorders/symptoms. Methods A systematic review of articles in the international literature published between 2003 and 2014 was performed in the electronic databases PubMed, PsycINFO, LILACS, and SciELO using the terms (chronic pelvic pain) AND (psychiatry OR psychiatric OR depression OR anxiety OR posttraumatic stress OR somatoform). The searches returned a total of 529 matches that were filtered according to predefined inclusion and exclusion criteria. A total of 18 articles were selected. Results The investigations focused mainly on the assessment of depression and anxiety disorders/symptoms, with rather high rates (17-38.6%). Depression and anxiety symptoms were more prevalent among women with CPP compared to healthy groups. Comparisons between groups with CPP and with specific pathologies that also have pain as a symptom showed that depression indicators are more frequent in CPP. Depressive symptoms tend to be more common in CPP and have no particular association with pain itself, the core feature of CPP. Discussion Other aspects of CPP seem to play a specific role in this association. Anxiety and other psychiatric disorders require further investigation so that their impact on CPP can be better understood.